The Priority of Application Regarding the Inheritance Provisions Differed between the Iraqi Personal Status Law and the Amended Law in the Kurdistan Region - Baram, Sadi Hassan (As-Siyasi: Journal of Constitutional Law, 2023)
This research examines the conflict arising from the differences in legal texts between the existing Iraqi Personal Status Law and the frequently amended laws in the Kurdistan Region. Furthermore, the issuance of amendments by the Kurdistan Region has exacerbated this conflict, leading to confusion and disputes between the two legal frameworks. The uncertainties surrounding the rationale behind these amendments have raised questions and doubts among legal practitioners and researchers, prompting a conservative approach within the courts. This study addresses and resolves these uncertainties by employing a comparative and analytical methodology. With a focus on constitutional and legal standards and the principle of justice, the research aims to clarify the applicability of either law. By undertaking this comprehensive analysis, the study endeavors to eliminate perceptions of ambiguity and hesitation, thereby contributing to a more cohesive legal landscape in the region. The research results show the fundamental difference between the Iraqi Personal Status Law and the amended law in the Kurdistan Region in matters of inheritance, specifically centered on the obligatory will and the wife's inheritance, and the Kurdish legislator made amendments in both issues, considering that amending federal laws is guaranteed to the regions by constitutional texts as long as they do not conflict with the constant provisions of Islam and the principles of democracy. This is not considered a departure from the 2005 Iraqi constitutional framework because the Federal Supreme Court, in its capacity as supervisor of the constitutionality of laws.